Analysis Factors that Related to Malnutrition of Children Under Five Years Old - Diah K Pranadji; . Retnaningsih; . Ruwiah (Media Gizi dan Keluarga, 2001)
The aim of the study was to analyze factors that related to malnutrition of children under five years old. The study had been conducted from July to September 2000 at Pagelaran, Ciomas Subdistrict, Bogor, West Java Province. The subjects were 60 underweight children who were selected from three Posyandu. The socioeconomic background of the family are as follows: the age of fathers are between 20 to 30 years old (38.3%) and mothers are between 20 to 25 years old (48.6%). The level of education of most fathers (55%) and mothers (75.7%) are elementary school. The family size of most subjects (66.7%) is categorized as small family ( income per capita per month is Rp 84,803.90, which about 43.9% families are categorized as middle class. The average of nutritional knowledge of mothers is 73% and most of them (55%) are categorized as sufficient. The average of energy consumption of children under five years is 745 kcal and the level of energy adequacy is 61.4%. About 56.7% children under five years are categorized as undernourished. The average of protein consumption of children under five years is 19.4 g and the level of protein adequacy is 84.3%. Most children (65%) are categorized as well nourished.There are 40% children under five years are underweight and 15% children are severe-underweight. About 39.5% children aged between 12 to 24 months and 53.8% children aged between 25 to 36 months are underweight, and 55.6% children aged 37 to 46 months are severe-underweight. The factors that related to malnutrition (level of energy and protein adequacy) of children under five years are family income level and nutritional knowledge of mothers.